2020
DOI: 10.11648/j.sjac.20200803.13
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Casein in Different Milk Samples

Abstract: Milk is an important part of human life and supposed to be a nutritious food which contain about 80% proteins. Milk proteins consist of 80% casein (soluble protein), 2-8% lactose (milk fat) and remaining is whey (byproduct of cheese and casein manufacture). Casein is more important and contain almost all essential amino acids. The purpose of the present work was to estimate the amount of casein in different milk samples including natural milk (cow, buffalo, sheep and goat) both in boiled and un-boiled form and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
3
1
Order By: Relevance
“…2). The amount of casein protein obtained in present study shows resemblance with the values of casein found by Jabeen et al [10] for milk samples of cow, buffalo and goat.…”
Section: Casein (G/100ml)supporting
confidence: 89%
See 2 more Smart Citations
“…2). The amount of casein protein obtained in present study shows resemblance with the values of casein found by Jabeen et al [10] for milk samples of cow, buffalo and goat.…”
Section: Casein (G/100ml)supporting
confidence: 89%
“…The method of precipitation of casein protein in milk by lowering the pH of milk to 4.6 (by using 2% HCl), the precipitated casein was filtered and dried in oven at 40˚C for 24 hours and then dry weight of casein was measured with digital balance. The same methodology was used by Patil et al [13], Jamil et al [14], Kumaresan et al [15], Jabeen et al [10].…”
Section: Fig 1 Location Map For Selected Sampling Sites Of South-west...mentioning
confidence: 99%
See 1 more Smart Citation
“…The content of casein previously reported was 28.26 mg/ml by Cozma et al (2011), 32.66 mg/ml by Maurmayr et al (2018), and 28.36 ml/ml by Amalfitano et al (2020), all the reported values being less than ≤ 50% group of cows (37.77 mg/ml), while greater than 25.61 mg/ml was found in the >87.5% group of cows in this study. Jabeen et al (2020) reported 4.91g (49.1 mg/ml) using acid precipitation methods in cow's milk in Pakistan; this is greater than the current study reported for all genetic groups. The value of whey protein previously reported was 6.99 mg/ ml by Maurmayr et al (2018) and 5.42 mg/ml by Amalfitano et al (2020); both reported results lower than 9.44 mg/ml found in ≤ 50% and higher than 4.54 mg/ml found in >87.5% of cows in this study.…”
Section: Effect Of Genetic Groupcontrasting
confidence: 83%
“…Casein precipitated, and the supernatant was decanted using 45µm filter paper and a funnel. The precipitate was washed with distilled water to remove the salts and then with ethanol to remove the remaining fats then dried and weighed (Jabeen et al, 2020). Whey protein was obtained by subtracting casein from total protein.…”
Section: Milk Analysismentioning
confidence: 99%